Building An Observational Network To Motor Excessive Among Middle School Students - Kecili , Djamal; Chouchane , Warda (sports creativity, 2025)
The importance of our study lies in building an observational network that can measure, identify the hyperactivity of middle stage students in sports and physical education classes and which can be applied in the field. We based the frame of our observational network on the Glickman model, Recording behavior by repetitions model, Recording behavior by Time intervals model. In this research paper, we have proposed a note card to detect hyperactivity behavior in the physical and sports education class, where the note card consisted of the date of the observation procedure, location, duration, procedural behavior, pupils' names and grades and contains three areas: impulsive attention deficit and opposing behavior This card aimed at measuring hyper motion behavior For middle school pupils, and the generalization of the use of this card in the future in the detection of hyperactivity, this card included in its final. We used a quantitative grading estimate where the hyperactivity behavior of an average first year pupil could be recorded accordingly. We concluded that the proposed behavioral procedures in the observational network measures hypermobility